Anatomy of lifetime earnings inequality: Heterogeneity in job ladder risk vs. human capital - Fatih Karahan; Serdar Ozkan; Jae Song (Federal Reserve Bank of New York, 2019)
We study the determinants of lifetime earnings (LE) inequality in the United States, for which differences in lifetime earnings growth are key. Using administrative data and focusing on the roles of job ladder dynamics and on-the-job learning, we document that 1) lower LE workers change jobs more often, mainly driven by higher nonemployment; 2) earnings growth for job stayers is similar at around 2 percent in the bottom two-thirds of the LE distribution, whereas for job switchers it rises with LE; and 3) top LE workers enjoy high earnings growth regardless of job switching. We estimate a job ladder model with on-the-job learning featuring ex ante heterogeneity in learning ability and job ladder risk - job loss, job finding, and contact rates. We find that learning ability differences explain almost all earnings growth heterogeneity above the median, whereas ex ante heterogeneity in job ladder risk accounts for 80 percent of LE growth differences below the median.
Keywords: E24; J24; J31; 330; job ladder; inequality; Pareto tails